2021
DOI: 10.1007/s12221-021-0069-z
|View full text |Cite
|
Sign up to set email alerts
|

New Composites from Waste Polypropylene/Eggshell Characterized by High Flame Retardant and Mechanical Properties

Abstract: This manuscript aimed to enhance the mechanical, ignition properties of polypropylene (PP). To reduce waste pollution of the environment, recycled waste polypropylene (WPP), and waste chicken eggshell (WCES) were used. WCES was used as a bio-filler to form new WPP composites. The effect of the addition of magnesium hydroxide (MOH) and monoammonium phosphate (MAP) on the properties of WPP/WCES composites has been studied. The structure of the composites was characterized by Fourier-transform infrared spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In addition, eggshell might improve the mechanical characteristics of PP composites while also functioning as a fireproof synergist. Younis et al [57] developed a product using recycled waste polypropylene (WPP) and waste chicken eggshell (WCES) as biofilters. Adding 10 phr of WCES to WPP/WCES composites increased their tensile and flexural strength by 15% and 8%, respectively, compared to WPP composites.…”
Section: Eggshellmentioning
confidence: 99%
“…In addition, eggshell might improve the mechanical characteristics of PP composites while also functioning as a fireproof synergist. Younis et al [57] developed a product using recycled waste polypropylene (WPP) and waste chicken eggshell (WCES) as biofilters. Adding 10 phr of WCES to WPP/WCES composites increased their tensile and flexural strength by 15% and 8%, respectively, compared to WPP composites.…”
Section: Eggshellmentioning
confidence: 99%
“…Influence of surface flame retardant layer containing ammonium polyphosphate and expandable graphite on the performance of jute/polypropylene composites, the results showed that the jute/PP composites with APP/EG-retardant layer were less flammable with higher LOI value, longer time to ignition, lower value of the peak heat release rate, total heat release, effective heat combustion, total smoke production, and became selfextinguished in HBR test [2]. New Composites from Waste Polypropylene/Eggshell Characterized by High Flame Retardant and Mechanical Properties, the results indicated that the 10 phr of the WCES enhanced the tensile strength and flexural strength of WPP/WCES composites by 15 and 8 % compared to the neat WPP composite, respectively [3]. Effect of hollow glass microsphere on the flame retardancy and combustion behavior of intumescent flame retardant polypropylene composites, the result of the LOI can be as high as 36.5% with only 1 WT% HGM and 24 WT% IFR addition.…”
Section: Introductionmentioning
confidence: 97%
“…Based on the existing literature, several attempts have been made to reinforce different types of polymers using waste eggshell powder including, but not limited to, polypropylene [8,16], high-density polyethylene [17,18], and lowdensity polyethylene [14]. However, to our knowledge, none of the previous studies has dealt with reinforcing polyamide 12 matrix with waste eggshells.…”
Section: Introductionmentioning
confidence: 99%